A kipande for Ugandans? The aborted 1947 ‘identity card for Africans’ - (:unkn) unknown (My University, 2021)
In October 1947 in Uganda, the British colonial administration opened local consultations about the introduction of an ‘identity card for Africans.’ The consultation process concluded barely two months later, putting a definitive end to the project. Through a thorough examination of Ugandan and British archives and the East African press of the time, this article traces the failure of this project. It shows how, despite different political and economic contexts, the Ugandan process was impacted by the debates about the much-detested Kenyan kipande. This case study shows the intra-imperial circulation of identification schemes, personnel, and techniques as well as the common attempt to impose a moral order of the identity card. It also highlights the limits and resistance of a regionalized elite to the export of a model of political, social, and economic control.
Keywords: African Research